RENDAHNYA KESADARAN MASYARAKAT TERHADAPPENDIDIKAN DI DESA TEGALLEGA - Nurjamilah, Lelah; Ukhrotunnasihah, Ukhrotunnasihah (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
Awareness of education in Indonesia is still very low, especiallyin remote areas. It is very unfortunate. In the midst of the era ofglobalization and modernization, the more sophisticated technology isstill a lot of people who do not appreciate how the importance ofeducation, especially in the education. Because highly educated peoplewill not have narrow thoughts about the future, they are orientedtoward their future. Highly educated people will also live with thenorms prevailing in society. They know what to do with their future, willnot give up or surrender to the circumstances. Conversely, people orparents who have a narrow mindset that considers educationunimportant, causing their children who do not receive education willbe a burden for the community. There are some objective issues thatmake people tend not to attach importance to religious education. Thefirst is ignorance of the importance of education for survival. Many ofthem rural communities who think narrowly about formal education ornon formal, whereaseducation plays an important role to support theirlives in the future. For that I have some solutions that can be done toreduce the low awareness of education. By way of socialization aboutthe importance of formal education and non formal for the life of civilsociety.